독일의 농업경영체등록과 세제지원 체계 - 김수석 (한국농촌경제연구원, 2013)
This paper aims to draw some implications from the German tax reduction program for agricultural holdings by examining its institutional configuration and operating system. In order to be recognized as an agricultural holding under the tax law, several steps need to be taken in the registration process. A newly founded agricultural holding should join agricultural social insurances and register its establishment with the tax office. The registered business entity then can receive various benefits such as tax reduction. A significant implication of the German system concerning the registration of an agricultural holding under the tax law is that it not only clarifies the requirements of a legitimate agricultural holding but also provides the foundation for the efficient tax policies such as Earned Income Tax Credit(EITC).
Keywords: 농업경영체; 독일 농업경영체등록; 세제지원; agricultural holding; German farm manager registration; tax reduction